Discontinuities in the electromagnetic field - Idemen, M. Mithat (Hoboken, N.J. : Wiley-IEEE Press, 2011)
'This book presents some new approaches and basic results connected with the discontinuities of the electromagnetic field. The discontinuities in question may be (1) the bounded jump discontinuities on the interfaces between two media or on the material sheets which model very thin layers or (2) unbounded values at the edge of wedge type structures or (3) unbounded values at the tips of conical structures. The book involves may examples as well as problems (exercises) to be solved by the readers'--
Includes bibliographical references (p. 215-218) and index.
Keywords: Electromagnetic fields -- Mathematics; Maxwell equations; Electromagnetic waves